Modesty in the Top Management Team: Investor Reaction and Performance Implications. (April 2017) - Ridge, Jason W.; Ingram, Amy
Much of the recent research on executive characteristics focuses on attributes that society tends to view negatively, such as self-interest, self-serving bias, and narcissism. While providing insights into how executives' impact organizational outcomes, there may be attributes more positively viewed by society present in top management teams (TMTs) that have been overlooked, specifically TMT modesty. Though modesty deviates from the conventional view of executives, evidence from social psychology suggests that modesty positively impacts career success and upward mobility, suggesting that at least some individuals that rise to the level of the TMT are more modest than previously expected. Building on this insight, we argue that TMT modesty both elicits positive investor reactions following earnings calls and corresponds with higher levels of firm performance.